Approach on thermoelectricity reliability of board-level backplane based on the orthogonal experiment design. (15th September 2010) - Zhang, Liqiang; Wu, Zhaohua; Xu, Xianxin; Xu, Haifeng; Wu, Yongsheng; Li, Pei; Yang, Ping
The objective of this paper is to provide a systematic investigation to orthogonal experiment design of backplane. The thermoelectricity reliability is systematically investigated by using mixed orthogonal array L9 (3, 4) based on orthogonal experimental design. The experiment results show that the wire width and wire pitch have a significant impact on the thermoelectricity reliability of the backplane, while the wire thickness has an unobtrusive effect. A finite element model of backplane is established based on a sample structure. The results show that the maximum stress occurred in the copper wire, which connected with FR-4 and the polyimide.